2019–2020 Bushfire impacts on sediment and contaminant transport following rainfall in the Upper Murray River catchment. (19th August 2021) - Biswas, Tapas K.; Karim, Fazlul; Kumar, Anu; Wilkinson, Scott; Guerschman, Juan; Rees, Gavin; McInerney, Paul; Zampatti, Brenton; Sullivan, Andrew; Nyman, Petter; Sheridan, Gary J.; Joehnk, Klaus
Abstract: During the 2019–2020 Australian bushfire season, large expanses ( 47%) of agricultural and forested land in the Upper Murray River catchment of southeastern (SE) Australia were burned. Storm activity and rainfall following the fires increased sediment loads in rivers, resulting in localized fish kills and widespread water‐quality deterioration. We collected water samples from the headwaters of the Murray River for sediment and contaminant analysis and assessed changes in water quality using long‐term monitoring data. A robust runoff routing model was used to estimate the effect of fire on sediment loads in the Murray River. Peak turbidity in the Murray River reached values of up to 4200 nephelometric turbidity units (NTU), shown as pitch‐black water coming down the river. The increase in suspended solids was accompanied by elevated nutrient concentrations during post‐bushfire runoff events. The model simulations demonstrated that the sediment load could be five times greater in the first year after a bushfire than in the prefire condition. It was estimated that Lake Hume, a large reservoir downstream from fire‐affected areas, would receive a maximum of 600 000 metric tonnes of sediment per month in the period immediately following the bushfire, depending on rainfall. Total zinc, arsenic, chromium, nickel, copper, and lead concentrations were above the 99% toxicant default guideline values (DGVs) for freshwater ecosystems. It is also likely that increased nutrient loads in Lake Hume will have ongoing implications for algal dynamics, in both the lake and the Murray River downstream. Information from this study provides a valuable basis for future research to support bushfire‐related policy developments in fire‐prone catchments and the mitigation of postfire water quality and aquatic ecosystem impacts. Integr Environ Assess Manag 2021;17:1203–1214. © 2021 Commonwealth of Australia. Integrated Environmental Assessment and Management © 2021 Society of Environmental Toxicology & Chemistry (SETAC). KEY POINTS: This study provides information useful to our understanding of bushfire impacts on water quality. Heavy rainfall after the fires discharged large volumes of ash and sediment into the Murray River, resulting in widespread deterioration of water quality and localized fish kills. Even six months after fires, runoff from the burned catchment was still carrying large amounts of sediments, nutrients, and carbon. The new modeling method can be applied elsewhere to prepare for the adverse effects of rain following a bushfire by minimizing sediment in runoffs.